Fisiologia térmica e balanço hídrico em anfíbios anuros - Bovo, Rafael Parelli [UNESP] (2015)
Temperature and water availability are factors that affect, importantly, the ecology, physiology, and behavior of amphibians. In this sense, these animals need to present a number of ecophysiological characteristics that allows them to cope with potentially challenging environmental features. In this thesis, I aimed to explore different topics (ecological gradients, diseases, and activity) focusing on the thermal physiology and water balance of anuran amphibians. The first chapter presents a general introduction focused on one of the central themes of this thesis, the thermal physiology of amphibians. However, this chapter also explores the inter-relationship between body temperature regulation and water balance. The second chapter investigates whether or not physiological traits associated to thermal tolerances and water balance, in five anuran amphibians, vary along elevational gradients along two mountain ranges, Serra do Mar and Serra da Mantiqueira, in the Brazilian Atlantic Forest. The third chapter examines the potential effects of chytridomycosis - an emerging fungal disease claimed to cause amphibian population declines and extinctions worldwide due to cutaneous osmoregulatory disorders - on the water balance and mortality of anuran species from Brazil. The fourth chapter investigates whether or not the diurnal activity of dispersing juveniles of the burrowing frog, Dermatonotus muelleri, might be correlated with physiological traits associated to thermal physiology and water balance